The politics of the European Green and Fair Transition: Italian parties’ voting behaviour in the European Parliament - Benedetta Cotta; Edoardo Bressanelli; Ivan Galligani; David Natali (Italian Political Science, 2024)
The consequences of increasing temperatures and of weather-related environmental disasters have become globally evident, including in the European Union (EU), where countries such as Italy have been recognized as being particularly vulnerable to climate change. As a response to these threats, the European Commission (EC) launched the European Green Deal in 2019 with the ambition of transforming the EU into a ‘fair and prosperous society with a modern, resource-efficient and competitive economy’ through a ‘socially just ecological transition’ by 2050 (EC 2019: 2). New policy instruments have been discussed and adopted at the European level to attain a Green and Fair Transition (GFT), such as the Social Climate Fund (SCF) created to support member states’ reduction of carbon emissions in the transport and building sectors. Despite a growing academic interest in the SCF in assessing the EC’s proposal and its environmental and social features, knowledge on the politics of the SCF remains limited. Building on research analysing the structure of party competition in the European Parliament (EP), this article investigates inter-party competition and coalition making on the adoption of the SCF. It does so by analysing voting behaviour on the SCF (draft and adopted) regulation, as discussed and voted for in the plenary sessions of the EP. The empirical focus is placed on Italian political parties, Italy being one of the major beneficiaries of the SCF but at the same time having recognised climate-related weaknesses and a lack of reform ambition on climate policies. Providing novel data on the politics behind the SCF, the article sheds light on the supporting coalitions as well as on the conflicts and synergies between Italian and other European political parties on green and fair transition matters.